Anti-corruption laws in Costa Rica. A perspective from the duty of integrity as an ethical exercise that prioritizes collective well-being over particular interests (Preprint) - Solano Villareal, Diana (2025)
This paper aims to diagnose, based on the principle of the duty of integrity as an ethical exercise that prioritizes collective well-being over private interests, the anti-corruption legislation specifically directed at the functioning of Costa Rican state institutions since the country joined the OECD.